Proximity to Fast Food Outlets and Supermarkets as Predictors of Fast Food Dining Frequency - Athens, Jessica K. (J Acad Nutr Diet, 2016)
BACKGROUND: This study used cross-sectional data to test the independent relationship of (1) proximity to chain fast food outlets and (2) proximity to full-service supermarkets on the frequency of meal-time dining at fast food outlets in two major urban areas, using three approaches to define “access.” Interactions between presence of a supermarket and presence of fast food outlets as predictors of fast food dining were also tested. METHODS: Residential intersections for respondents in point-of-purchase and random-digit-dial telephone surveys of adults in Philadelphia and Baltimore were geocoded. The count of fast food outlets and supermarkets within quarter-mile, half-mile, and one-mile street network buffers around each respondent’s intersection was calculated, as well as distance to the nearest fast food outlet and supermarket. These variables were regressed on weekly fast-food dining frequency to determine if proximity to fast food and supermarkets had independent and joint effects on fast-food dining. RESULTS: The effect of access to supermarkets and chain fast food outlets varied by study population. Among telephone survey respondents, supermarket access was the only significant predictor of fast food dining frequency. Point-of-purchase respondents were generally unaffected by proximity to either supermarkets or fast food outlets. However, ≥1 fast food outlet within a 1-mile buffer was an independent predictor of more fast food meals among point-of-purchase respondents. At ¼-mile distance, ≥1 supermarket was predictive of fewer fast food meals. CONCLUSIONS: Supermarket access was associated with less fast food dining among telephone respondents while access to fast food outlets were associated with more fast food visits among survey respondents identified at point-of-purchase. This study adds to the existing literature on geographic determinants of fast food dining behavior among urban adults in the general population and those who regularly consume fast food.